2001
DOI: 10.2190/pxug-j0t8-dguk-08md
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver and Elder Experiences of Cambodian, Vietnamese, Soviet Jewish, and Ukrainian Refugees

Abstract: Our purpose was to describe and compare Cambodian, Vietnamese, Soviet Jewish, and Ukrainian refugee caregivers and elders on life experiences, health status, and knowledge of available services. Detailed interviews were conducted with 105 female caregivers and 52 elders. Similar patterns emerged across all groups with regard to filial obligation, minimal knowledge of services, impact of immigration, and retention of cultural ties. Findings confirmed the special health and social service needs of refugee famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 51 publications
2
21
0
1
Order By: Relevance
“…This approach includes the use of mental health services based in schools and community agencies (Fazel & Stein, 2002) as well as community screening and preventive programs (Kataoka et al, 2003;Kennedy, Seymour, & Hummel, 1999;Palinkas et al, 2003). A similar communitybased and naturalistic approach may be necessary to met the challenges of providing mental health services for elder immigrants, especially in the context of traditions of family caregiving conflicting with changing family structure and cohesion (Strumpf, Glicksman, Goldberg-Glen, Fox, & Logue 2001).…”
Section: Mental Health Services For Immigrants and Refugeesmentioning
confidence: 99%
“…This approach includes the use of mental health services based in schools and community agencies (Fazel & Stein, 2002) as well as community screening and preventive programs (Kataoka et al, 2003;Kennedy, Seymour, & Hummel, 1999;Palinkas et al, 2003). A similar communitybased and naturalistic approach may be necessary to met the challenges of providing mental health services for elder immigrants, especially in the context of traditions of family caregiving conflicting with changing family structure and cohesion (Strumpf, Glicksman, Goldberg-Glen, Fox, & Logue 2001).…”
Section: Mental Health Services For Immigrants and Refugeesmentioning
confidence: 99%
“…It has been found that many Eastern Europeans tend to have universal and inexpensive access to health services in their native countries [23,65] and tend to utilize health services in a pattern similar to that used in their native countries [64]. Thus, an Eastern European woman who is used to physician-administered services for screening may seek to utilize that method (regardless of the fact that such access in the US is limited), and engage in lower frequencies of self-administered preventive practices.…”
Section: Breast Self-examination Among Subpopulations Of Womenmentioning
confidence: 99%
“…Some studies have documented that older Vietnamese refugees have more adjustment and language acculturation problems than their younger counterparts (Strumpf, Glicksman, Goldberg-Glen, Fox, & Logue, 2001;Tran, 1990). Many elders reported a sense of loss and dislocation, along with feelings of linguistic and cultural isolation from mainstream American society (Strumpf et al, 2001).…”
mentioning
confidence: 99%
“…Many elders reported a sense of loss and dislocation, along with feelings of linguistic and cultural isolation from mainstream American society (Strumpf et al, 2001). There are little data on their health-related quality of life (HRQOL).…”
mentioning
confidence: 99%